Perceived income and food security challenges during COVID-19 in informal settlement households in Windhoek practising urban agriculture - Susanna Shivolo-Useb; Cecil Togarepi; Joel Muzanima; Maria N. T. Shipandeni; Cecilie N. Jona; Ndiilokelwa P. Petrus (Discover Global Society)
Abstract Food insecurity and insufficient household income are among the major challenges faced by inhabitants of informal settlements globally. Urban agriculture provides food and income for many informal settlement households. However, during the COVID-19 pandemic, many operations were disrupted and measures implemented to curb the spread led to food insecurity and income losses. This study sought to determine the impact of COVID-19 on the income and food security of urban agricultural households in informal settlements in Windhoek, Namibia. A survey was conducted to obtain information on urban agriculture, income, food security, socioeconomic demographics and COVID-19challenges. HFIAS was used to assess the food insecurity status of households, and an ordered logit model was used to determine the factors influencing food insecurity among urban agricultural households. The findings revealed that the number of respondents who earned more than N$4000 per month decreased income by 7.3%, those who earned less than N$1000 increased by 8% during the COVID-19 period. Closure of open markets and employment losses are the main causes of income change. Most respondents (71.2%) were food insecure and only (28.2%) were food secured during the pandemic. Secondary education and business ownership are associated with lower food insecurity in households and are significant at p  < 0.05, whereas unemployment is associated with higher food insecurity levels ( p  < 0.05). Urban agriculture was the main coping strategy (82.2%) during the pandemic, suggesting a need to support households in informal settlements to produce their own food for self-sufficiency and livelihood security.